Insertion of an unstable element in an intervening sequence of maize Adh1 affects transcription but not processing. - Rowland, L J (1985)
Three independently isolated and unstable mutants of the maize alcohol dehydrogenase 1 gene (Adh1) have arisen by insertion of the Mu transposing element into the first intervening sequence of the progenitor Adh1 allele. The mutants have been selected for their decreased levels of alcohol dehydrogenase 1 activity. The original mutants were unstable, giving rise to both revertant alleles and altered mutant alleles. From one of the original mutants, two derivative mutants have been recovered and described. We analyzed the effect of Mu insertion in all five of these mutants by measuring relative levels of run-off transcripts from the progenitor and mutant alleles and by comparing levels of run-off transcripts corresponding to regions lying 5' and 3' to the insertion sites. In this paper we present evidence that early transcriptional events are affected, but that, in spite of the inclusion of a 1.4-kilobase transposing DNA element, processing of transcripts occurs normally.